2022
DOI: 10.1111/1440-1681.13645
|View full text |Cite
|
Sign up to set email alerts
|

Icariin attenuates ischaemic stroke through suppressing inflammation mediated by endoplasmic reticulum stress signalling pathway in rats

Abstract: Ischaemic stroke possesses the characteristics of high incidence, high disability and high mortality. Icariin (ICA) is a flavonoid extracted from the traditional Chinese medicine Epimedium. The protective effect of ICA on ischaemic stroke is worthy of further study. In this study, male Sprague-Dawley rats were randomly divided into the following seven groups: sham, model, ICA low-dose (10 mg/kg), ICA medium-dose (20 mg/kg), ICA high-dose (40 mg/kg), positive control drug (12 mg/kg nimodipine) and endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, efficacious agents to conquer CIRI should own potent antineuroinflammation and antioxidant activities. Previous research has found that the main active compounds of EA, namely ICA, ICS II, and ICT, can effectively penetrate the bloodbrain barrier and demonstrate potent anti-neuroinflammatory and antioxidant activities against multiple diseases [10,12,19,20]. The above-mentioned scenario and pharmacological properties of EP prompted us to excavate the therapeutic effect and its possible targets of EP on CIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efficacious agents to conquer CIRI should own potent antineuroinflammation and antioxidant activities. Previous research has found that the main active compounds of EA, namely ICA, ICS II, and ICT, can effectively penetrate the bloodbrain barrier and demonstrate potent anti-neuroinflammatory and antioxidant activities against multiple diseases [10,12,19,20]. The above-mentioned scenario and pharmacological properties of EP prompted us to excavate the therapeutic effect and its possible targets of EP on CIRI.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition to conventional vascular risk factors, such as hypertension, diabetes, long-term smoking and drinking and hyperlipidaemia, recent studies have found that inflammation is closely connected to cerebral infarction. [20][21][22] In clinical terms, tuberculosis is a common chronic inflammatory disease. Although tuberculosis meningitis comprises 1% of the incident cases of tuberculosis, it remains the most serious form of extrapulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2 h/22 h I/R rat model of MCAO, a dose of 200 mg/kg curcumin can reduce the expression of pro-inflammatory factors IL-6, TNF-α and iNOS by inhibiting the TLR4/p38/MAPK pathway, thereby inhibiting inflammatory response and improving brain injury and nerve function ( Huang et al, 2018 ). Icariin ( Zheng et al, 2022 ), diosgenin ( Zhang et al, 2022 ), and syringin ( Liu et al, 2022 ) administered in the MCAO rat model, improved brain injury and neurologic function by downregulating pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 to inhibit the inflammatory response.…”
Section: Protective Mechanism Of Traditional Chinese Medicine Monomer...mentioning
confidence: 99%